Qazwini-Baghdadi Intellectual Convergence Through (AL TADWEEN FI AKHBAR QAZWIN) Book: Scholars of tradition as model - Al-Shimmari, Jinan Ali (Al-Adab Journal, 2021)
This research has studied the Qazwini-Baghdadi Intellectual Convergence Through (AL TADWEEN FI AKHBAR QAZWIN) Book to Abi Al-Qasim Abdulkareem Al-Rafeai (623 AH-1226AD) Scholars of tradition as model. Qazwin city in the past fourth century has reached to developed level of scientific recovery which is made it beacon of science. Many factors gathered and helped this recovery as security and stability that the Qazwin scholars found and settled in it , this was the most important factors which helped to establish many sciences and knowledge centers and recovery the scientific movement where it became a place science askers and men of scholars of tradition . The scientific and cultural relationships between Qazwin and Baghdad the capital of Arab-Islamic State helped to appear many scholars of tradition who are recording what they see and registering what they notice. They left many works to the researchers in Arab-Islamic studies as it is a reliable source to the present time. The local books filled many scholars' names and this what we found in (AL TADWEEN FI AKHBAR QAZWIN) Book to Al-Rafeai. Many scholars of Qazwin emerged in Baghdad and confirmed one of its intellectual side, especially when they took office an important position as judge and teacher in Al- Nizamiyya of Baghdad an example. So, they are not only a visitor or stable but they merged in the life in all important levels and fed their output Islamic intellectual movement.